PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL, DAN LOVE OF MONEY TERHADAP PERSEPSI MAHASISWA MENGENAI ETIKA PROFESI AKUNTAN - Ruli Aprilianto; Tarmizi Achmad (Diponegoro Journal of Accounting, 2017)
This objective of this research is to examine the influence of emotional intelligence, intellectual intelligence and love of money toward students’ perception of professional accounting ethics. The sample in this study were taken using purposive sampling method of data collection with the criteria of the respondents had taken courses in Management Accounting, Auditing Accounting I and Practicum Accounting. The population of this study is the undergraduate Accounting students in Diponegoro University with a total population of 320 people, with 96 people were chosen as samples. Data analysis was performed with descriptive statistics, classical assumption and hypothesis testing of regression method using SPSS version 21. The empirical results of this study show that both emotional intelligence and intellectual intelligence have significantly positive influence toward students’ perception of professional accounting ethics while love of money has a negatively non-significant influence toward students’ perception of professional accounting ethics.